The critical success factors of waqf land development for sustainable agriculture - Amal Hayati Ishak; Siti Nor Amira Mohamad; Siti Khadijah Ab Manan; Muhamad Hasif Yahaya; Wan Naimah Wan Daud; Dziauddin Sharif (Social Sciences and Humanities Open)
Amidst the food security issue worldwide, developing waqf land for agriculture is essential as it could help in preparing sufficient food supply for the nation. In Malaysia, a considerable amount of waqf land is reported undeveloped, unfortunately contravening to the spirit of waqf in generating sustained benefit. In fact, in Islamic finance, waqf is promoted as a social finance instrument with the potentials in creating value for the society and environment, whilst providing financial returns. As the sole trustee of waqf property in the country, the State Islamic Religious Councils (SIRCs) should take all reasonable means to develop the property. Hence, this study analyses the critical success factors (CSF) to develop waqf land for agriculture, that are significant in providing meaningful insights for waqf trustees to plan for a productive and sustainable waqf development. Data was collected via Focused Group Discussion (FGD) attended by experts from the academia and industry. Employing a thematic analysis performed through Atlas ti, findings revealed five factors that are agreed capable in sustaining the benefits of waqf, appreciating the donor while assisting waqf trustees in executing trusts.